ASPECTE ALE STATUTULUI OXIDOREDUCĂTOR LA DIFERITE GENOTIPURI DE FLOAREA-SOARELUI ATACATE DE LUPOAIE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2007)
Accumulation of H2O2 and the activity of catalase in different genotypes of sunflower attacked by broomrape have been analyzed in this work. The accumulation of H2O2 in normal conditions is specified by genotype, being more active in the Xenia variety. The attack by broomrape leads to the intensification of the H2O2 synthesis in the analyzed genotypes, in particular in the Valentino variety. The activity of catalase decreases in attacked plants of the Xenia and Valentino varieties at the level of leaves as a result of the accumulation of SRO. The quantity of H2O2 correlates with the quantity of enzyme, both in normal conditions and in the plants attacked by broomrape.